The Qur’an and The Big Bang Theory: Regarding How Science Converges Divine Revelation on the Creation, Persistence, and Destruction of The Universe - Mu’adz D’Fahmi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2004)
This article seeks to find a synthesis between scientific discoveries (astronomical study) and the exposition of the Qur’an (Qur’anic study) by presenting theories of the Big Bang.